2010
DOI: 10.4171/jems/200
|View full text |Cite
|
Sign up to set email alerts
|

The genera, reflexibility and simplicity of regular maps

Abstract: Abstract. This paper uses combinatorial group theory to help answer some long-standing questions about the genera of orientable surfaces that carry particular kinds of regular maps. By classifying all orientably-regular maps whose automorphism group has order coprime to g −1, where g is the genus, all orientably-regular maps of genus p+1 for p prime are determined. As a consequence, it is shown that orientable surfaces of infinitely many genera carry no regular map that is chiral (irreflexible), and that orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(84 citation statements)
references
References 20 publications
3
80
1
Order By: Relevance
“…It would be interesting to characterise the genera with this property. Conder, Siráň and Tucker [5] have shown that there are no chiral maps of genus g = p+1 for primes p such that p − 1 is not divisible by 3, 5 or 8, but finding a similar result for hypermaps would seem to be more difficult.…”
Section: Casementioning
confidence: 99%
“…It would be interesting to characterise the genera with this property. Conder, Siráň and Tucker [5] have shown that there are no chiral maps of genus g = p+1 for primes p such that p − 1 is not divisible by 3, 5 or 8, but finding a similar result for hypermaps would seem to be more difficult.…”
Section: Casementioning
confidence: 99%
“…The corresponding quasiplatonic surfaces X, of genus p+1, are constructed in §3, Examples (i) -(iii) [1], and the associated maps, regarded by duality as dessins of type q, 2, r , are studied in Theorem 3.1 of [5].…”
Section: Problems Conjectures and Infinite Familiesmentioning
confidence: 99%
“…In [2], for example, some ground-breaking work by Breda, Nedela, andŠiráň [2] showed that there are no regular maps at all on non-orientable surfaces of Euler characteristic −p where p > 13 is prime and p ≡ 1 mod 12. We took a different approach in [13], to obtain a shorter proof of the latter, and also to prove that:…”
Section: Remaining Gaps In the Spectrummentioning
confidence: 99%